Governance Analysis of PT Asuransi Jiwasraya from the Perspective of Good Corporate Governance and Public Trust in Indonesia - Tri Hendarto, Deny (Journal of Economics and Business UBS, 2025)
The financial scandal involving PT Asuransi Jiwasraya has become emblematic of systemic governance failure within Indonesia’s insurance sector, triggering a public trust crisis toward state-owned financial institutions. This study aims to analyze the relationship between the implementation of Good Corporate Governance (GCG) principles and public trust levels, using Jiwasraya as a case study, while also evaluating the effectiveness of regulatory oversight in the insurance industry. Employing a narrative literature review combined with a case study approach, this research draws on secondary data sourced from open-access scholarly literature published within the last five years. The synthesis reveals that violations of transparency, accountability, and independence within Jiwasraya’s governance structure were the primary triggers for risky investment practices and financial report manipulation. It also finds that weak regulation and ineffective external oversight intensified the governance failure’s impact, resulting in a broader public trust crisis in the national insurance industry. This research contributes conceptually by highlighting that GCG must be implemented not only structurally but also socially to establish institutional legitimacy. Its practical implications emphasize the need to enhance regulatory capacity, improve public information disclosure, and develop more adaptive regulatory reforms to address reputational risks and the dynamic nature of Indonesia’s financial sector.